Biogeochemical Gradients in a Serpentinization‐Influenced Aquifer: Implications for Gas Exchange Between the Subsurface and Atmosphere. Issue 8 (11th August 2021) - Sabuda, Mary C.; Putman, Lindsay I.; Hoehler, Tori M.; Kubo, Michael D.; Brazelton, William J.; Cardace, Dawn; Schrenk, Matthew O.
Abstract: Serpentinization involves the hydration and alteration of ultramafic rocks, which produces hydrogen (H2 ) and methane (CH4 ) and results in distinctive groundwater chemistries. As reacted fluids mix with recharging surface water, gradients in chemistry and microbiology develop in the subsurface. We present a comprehensive analysis of biogeochemical gradients in the water column of a serpentinite‐hosted well, CSW1.1, at the Coast Range Ophiolite Microbial Observatory (CROMO) in California, USA. Samples for geochemistry, 16S rRNA gene sequencing, and metagenomics were collected at four discrete depths from the top of the well corresponding to 100%, 50%, 15%, and 0% of atmospheric oxygen (O2 ) levels, and from the well base at 19.5 m depth. Gibbs energy calculations assessed the energy available for a suite of reactions coupled to O2, sulfate (SO4 2− ), and nitrate (NO3 − ). Metagenomic data from the profile was used to construct metagenome assembled genomes (MAGs) to evaluate the completeness of biochemical pathways and compare the relative abundance of key diagnostic genes. Bioenergetic data point to the favorability of CH4 oxidation reactions despite little genetic evidence for this. Amplicon sequencing results highlight the abundance of key taxa affiliated with the genera Truepera, Serpentinomonas, and Dethiobacter . Although concentrations of NO3 − and H2 are low, genes for NO3 − reduction and oxidation of H2 and carbon monoxide (CO) were found in high abundance. Conceptual modeling results demonstrate the net depletion of H2 and CO in the groundwater, the consumption of CO2 and O2, and the potential for CH4 emission into the atmosphere at this terrestrial site of serpentinization. Plain Language Summary: Microorganisms living in extreme habitats on Earth generate energy by catalyzing chemical reactions using the compounds available. A water‐rock interaction known as serpentinization creates high pH and low‐oxygen waters, and a limited number of compounds for energy generation. Hydrogen, carbon monoxide, and methane are gases produced through serpentinization that may be used by microorganisms. To unravel small‐scale subsurface processes, we studied a depth profile from a serpentinization‐influenced groundwater well, and sampled the water at five depths. We measured chemical components of the groundwater (anions, dissolved gases), and calculated the energy available to organisms using a set of common metabolic reactions. We also assessed the microbial communities present, and determined their potential contributions to biogeochemical cycles. We found that three taxa, Serpentinomonas, Truepera, and Dethiobacter dominated. Despite high methane concentrations, genes for methane oxidation were absent throughout the profile. Rather, genes associated with the use of low abundance compounds, like carbon monoxide, hydrogen, and nitrate, were prevalent. This implies that carbon monoxide and hydrogen consumption can deplete these compounds before they reach the surface, and the lack of methane consumption may enable its release into the atmosphere. This work provides insight into the biogeochemical processes mediated by subsurface microorganisms in serpentinization‐influenced groundwater. Key Points: Chemical and bioenergetic gradients in ultrabasic groundwater change with depth in well CSW1.1 Bioenergetic reactions yielding the most energy are incongruent with the functional capabilities encoded within metagenomic data 16S rRNA gene sequence data and metagenome assembled genomes reveal that CSW1.1 is dominated by Serpentinomonas, Truepera, and Dethiobacter